A New and correct map of the British colonies in North America comprehending eastern Canada with the province of Quebec, New Brunswick, Nova Scotia, and the Government of Newfoundland : with the adjacent states of New England, Vermont, New York, Pennsylvania and New Jersey - Laurie & Whittle (Laurie & Whittle, 1794)
This is a 1794 map of northeastern North America from eastern Canada to Maryland. It shows degrees of latitude and longitude, sea banks, boundaries of states, waterways, and native American settlements. Decorative cartouche includes a beaver. Scale approximately 1:3,700,000. Relief shown pictorially. Shows degrees of latitude and longitude, sea banks, boundaries of states, waterways, and native American settlements. Includes historical notes. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ .